Pengaruh Fear of Missing Out (Fomo) dan Self-Control Terhadap Penggunaan Pinjaman Online Pada Mahasiswa Gen Z - Permatasari, Lintang Putri; Yuhertiana, Indrawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to evaluate the extent to which Fear of Missing Out (FoMO) and self-control influence the use of online loan services among Generation Z students in Surabaya. With the rising prevalence of online borrowing behavior in digital environments, understanding the psychological factors behind such behavior has become increasingly relevant. This research investigates whether these two individual factors, FoMO and self-control, simultaneously shape students’ financial decisions in the context of easy online loan access. The results show that FoMO has a positive and significant effect on online loan usage (p = 0.000; t = 13.098; β = 0.606), indicating that students with higher FoMO are more likely to engage in impulsive borrowing. Likewise, self-control also has a significant negative effect (p = 0.000; t = 7.706; β = 0.269), suggesting that higher levels of self-control reduce the likelihood of using online loans. Together, FoMO and self-control explain 48% of the variance in online loan usage. However, financial literacy does not significantly moderate the relationship between either FoMO (p = 0.949) or self-control (p = 0.092) and online loan use. The findings reveal that FoMO has a positive and significant effect on online loan usage (p = 0.000; t = 11.231; β = 0.581), suggesting that students with higher FoMO tendencies are more likely to use online loans. Financial literacy also shows a significant negative influence (p = 0.008; t = 2.668; β = -0.298), indicating that greater financial knowledge tends to reduce online loan use. However, self-control was found to have no significant effect (p = 0.729), nor did financial literacy significantly moderate the relationship between FoMO (p = 0.949) or self-control (p = 0.092) and online loan usage. These findings suggest that emotional and social pressures (such as FoMO) may outweigh rational financial decision-making, even among financially literate individuals. The study concludes that FoMO and self-control significantly influence online loan usage among Generation Z students, with FoMO having a stronger effect. Financial literacy does not moderate these relationships. Therefore, financial education should also address emotional and social factors, not just financial knowledge.